Faktor-Faktor Yang Mempengaruhi Terjadinya Kerawanan Pangan - Taslim Taslim; Ratnawati Tahir; Jumiati Lira (Jurnal Sosial Ekonomi Pertanian, 2023)
This study aims to assess the factors that cause food insecurity and find solutions to the factors that cause food insecurity in Ujung Labuang Village, Suppa District, Pinrang Regency, South Sulawesi. The respondents invited 32 people, and 5 key informants. The analytical method was multiple linear regression analysis The results of the analysis showed that from 5 indicators studied, there were three indicators that affected food insecurity and became a contributing factor to food insecurity in Ujung Labuang Village, namely the area of ​​agricultural land worked (0,12213385), the number of food supply facilities and infrastructure (0,132531849), and household income levels (0,178992577), while the level of the conditions of transportation facilities (- 0,18453267), the level of household income of the proportion of household expenditure (- 0,30416651) has no influence on the causative factors of food insecurity. The recommended solution is food fulfillment for poor and food insecure groups through an empowerment approach involving the participation and active role of all stakeholders and communities. Utilization of yard land by planting local food commodities can be used as the alternative food substitute for rice.